The effect of bone allografts combined with bone marrow stromal cells on the healing of segmental bone defects in a sheep model - Fernandes, Marco Bernardo C (BioMed Central, 2014)
BACKGROUND: The repair of large bone defects is a major orthopedic challenge because autologous bone grafts are not available in large amounts and because harvesting is often associated with donor-site morbidity. Considering that bone marrow stromal cells (BMSC) are responsible for the maintenance of bone turnover throughout life, we investigated bone repair at a site of a critically sized segmental defect in sheep tibia treated with BMSCs loaded onto allografts. The defect was created in the mid-portion of the tibial diaphysis of eight adult sheep, and the sheep were treated with ex-vivo expanded autologous BMSCs isolated from marrow aspirates and loaded onto cortical allografts (n = 4). The treated sheep were compared with control sheep that had been treated with cell-free allografts (n = 4) obtained from donors of the same breed as the receptor sheep. RESULTS: The healing response was monitored by radiographs monthly and by computed tomography and histology at six, ten, fourteen, and eighteen weeks after surgery. For the cell-loaded allografts, union was established more rapidly at the interface between the host bone and the allograft, and the healing process was more conspicuous. Remodeling of the allograft was complete at 18 weeks in the cell-treated animals. Histologically, the marrow cavity was reestablished, with intertrabecular spaces being filled with adipose marrow and with evidence of focal hematopoiesis. CONCLUSIONS: Allografts cellularized with AOCs (allografts of osteoprogenitor cells) can generate great clinical outcomes to noncellularized allografts to consolidate, reshape, structurally and morphologically reconstruct bone and bone marrow in a relatively short period of time. These features make this strategy very attractive for clinical use in orthopedic bioengineering.